NO Network for Plant–Microbe Communication Underground: A Review - Pande, Anjali; Mun, Bong-Gyu; Lee, Da-Sol; Khan, Murtaza; Lee, Geun-Mo; Hussain, Adil; Yun, Byung-Wook (Frontiers in Plant Science, 2021)
Mechanisms governing plant-microbe interaction in the rhizosphere attracted a lot of investigative attention in the last decade. The rhizosphere is not simply a source of nutrients and support for the plants, it is rather an ecosystem teeming with diverse flora and fauna including different groups of microbes that are useful as well as harmful for the plants. Plant microbe interaction occurs via a highly complex communication network that involves sophisticated machinery for the recognition of friend and foe at both sides. On the other hand, nitric oxide (NO) is a key, signaling molecule involved in plant development and defense. Studies on legume-rhizobia symbiosis suggest the involvement of nitric oxide during recognition, root hair curling, development of infection threads, nodule development, and nodule senescence. A similar role of NO is also suggested in the case of plant interaction with the mycorrhizal fungi. Another, insight into the plant-microbe interaction in the rhizosphere comes from the recognition of pathogen/microbe-associated molecular patterns (PAMPS/MAMPS) by the host plant and thereby NO-mediated activation of the defense signaling cascade. Thus, NO plays a major role in mediating the communication between plants and microbes in the rhizosphere. Interestingly, reports suggesting the role of silicon in increasing the number of nodules, enhancing nitrogen fixation, and also the combined effect of silicon and NO may indicate a possibility of their interaction in mediating microbial communication underground. However, the exact role of NO in mediating plant-microbe interaction remains elusive. Therefore, understanding the role of NO in underground plant physiology is very important, especially in relation to the plant’s interaction with the rhizospheric microbiome. This will help devise new strategies for protection against phytopathogens and enhancing plant productivity by promoting symbiotic interaction. This review focuses on the role of NO in plant-microbe communication underground.